Medicinal plants for digestive system disorders in Tebing Batu Village, Sambas District, West Kalimantan, Indonesia - RUQIAH GANDA PUTRI PANJAITAN; AGUS KURNIASI; EKO SRI WAHYUNI; HURRIAH DEWI SARTIKA PANJAITAN; KURNIA NINGSIH; TITIN TITIN; SHOKHAN SHARIF ALI (Society for Indonesian Biodiversity, 2025)
Abstract. Panjaitan RGP, Kurniasi A, Wahyuni ES, Panjaitan HDS, Ningsih K, Titin, Ali SS. 2025. Medicinal plants for digestive system disorders in Tebing Batu Village, Sambas District, West Kalimantan, Indonesia. Biodiversitas 26: 5647-5658. Disorders in the digestive system occur when the organs involved in the digestive process experience problems, which can disrupt their function and lead to symptoms such as bloating, diarrhea, gastritis, and Gastroesophageal Reflux Disease (GERD). One treatment for addressing digestive system disorders is the use of medicinal plants. This study aimed to inventory and document the use of medicinal plants for treating digestive system disorders by the community of Tebing Batu Village, Sebawi Sub-district, Sambas District, West Kalimantan, Indonesia. The method used in this study was qualitative descriptive. This study employed a qualitative method using purposive sampling as the selected technique. The results of the study indicate that there are 17 species of medicinal plants used to treat digestive system disorders, which include kalimaok (Ageratum conyzoides), sirsak (Annona muricata), pendaraan (Cyanthillium cinereum), kunyit (Curcuma longa), durian (Durio zibethinus), maram dapat (Elephantopus scaber), kencur (Kaempferia galanga), singkong (Manihot esculenta), cengkodok (Melastoma malabathricum), mengkudu (Morinda citrifolia), pandan (Pandanus amaryllifolius), ambing buah (Phyllanthus amarus), sirih (Piper betle), singkil (Premna serratifolia), jambu biji (Psidium guajava), sapu cina (Scoparia dulcis), saudagar (Struchium sparganophorum), which are classified into 13 families, with the most represented family being Asteraceae. The most commonly treated digestive disorders using the plants are stomachache and diarrhea. The most commonly used part is the leaf, while the most common processing technique is pounding. This study highlights the richness of local community knowledge in utilizing medicinal plants to treat digestive disorders. This study highlights the community's close relationship with nature and the importance of preserving local knowledge to be passed down to future generations.